2019
DOI: 10.47408/jldhe.v0i14.489
|View full text |Cite
|
Sign up to set email alerts
|

Making use of students' digital habits in higher education: What they already know and what they learn

Abstract: Varieties of digital practices have increasingly become part of people’s everyday lives and people, in general, use these communicative practices on a daily basis, mostly for social and entertaining purposes. As to higher education, researchers have pointed out that digital technology could be a useful tool in how to learn more effectively, if it is based on the abilities that students bring with them into higher education from their everyday life (for example, Buzzard et. al., 2011). In this case study, we ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…In a similar manner to the students in Hansson and Sjöberg's (2019) study, our students confirmed that, whilst they may have grown up with high levels of exposure to digital media, they still went through a process of developing strategies and techniques for working with digital texts in an academic context. Almost all of the students had developed their practices for studying from digital texts on their own through trial and error, or by talking to peers.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In a similar manner to the students in Hansson and Sjöberg's (2019) study, our students confirmed that, whilst they may have grown up with high levels of exposure to digital media, they still went through a process of developing strategies and techniques for working with digital texts in an academic context. Almost all of the students had developed their practices for studying from digital texts on their own through trial and error, or by talking to peers.…”
Section: Discussionsupporting
confidence: 65%
“…For example, Jones and Healing's (2010) research focused on first-year students' transition to university and concluded that the lack of homogeneity within the cohort in terms of previous experience of technology meant that making blanket assumptions related to age and digital proficiency was problematic. Furthermore, Hansson and Sjöberg (2019) found that, although students arrive at university with prior digital Journal of Learning Development in Higher Education, Issue 24: September 2022 3 experiences, they continue to develop their digital skills during their studies, particularly in relation to using software and critically evaluating digital sources.…”
Section: Literature Reviewmentioning
confidence: 99%